Preventing Dental Cavities with Mouth Rinsing Song for Elementary School Students, Sawahan District, Surabaya City - Hutapea, Yohana Vita Melodi; Andiyani, Intan; Nuradiyah, Fanny; Yusticia, Ica; Hidayanto, Agung Ridwan; Pramita, Anggi; Fadila, Vivin Dwi; Syarifah, Indi Mazaya; Fatah, Rizki Amelia; Halim, Muhammad; Susanti, Dwi; Sosiawan, Agung (Indonesian Journal of Dental Medicine, 2019)
Background: Dental and oral health is one of the public health indicators. Dental and oral health problems decrease individual health function. A lack of mouth rinsing causes dental and oral health problems in children after consuming sweet food. Dental health promotion can help the children learn about mouth rinsing and encourage them to have it regularly. MisDent is an educational program about dental health designed for children. We demonstrated and promoted mouth rinsing to the students, especially after they confused sweet food. Purpose: To promote correct tooth brushing to children and help monitoring student's dental health partnering with the local public health center. Methods: The program used dental health promotion strategies Patemon 2 Elementary School. We evaluated the program as well. Results: About 60% of students at Petemon 2 Elementary School were able to answer the questions correctly, have mouth rinsing correctly, memorize the "REK KUMUR REK” song. Conclusion: "MisDent” involved the first and second-grade students of Patemon 2 Elementary School. The program was expected to help to educate the students about dental and oral health.